2022
DOI: 10.11591/ijeecs.v26.i1.pp404-413
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for prediction of diabetes mellitus using deep convolutional neural network and long short-term memory

Abstract: Hyperglycemia arises due to diabetes mellitus, which is a persistent and life-threatening ailment. In this paper deep convolution neural network can be embedded to long short-term memory networks to recognize early prediction of diabetes and to decrease the complications that can be occurred through diabetes irrespective to the age. Diabetes problem is being gradually growing and presently, it is reported as a significant cause of death in the top spot. According to the recent studies 48% of overall world popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Sailasya and Kumari (2021) analyzed the performance of stroke prediction using ML classification algorithms moreover, supervised backpropagation is applied to the training dataset to fine-tune the network. Kumari et al (2022) presented a novel method for the prediction of diabetes mellitus using deep CNN and long shortterm memory. Rajeswari et al (2019) designed a scheme that relies on Machine learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sailasya and Kumari (2021) analyzed the performance of stroke prediction using ML classification algorithms moreover, supervised backpropagation is applied to the training dataset to fine-tune the network. Kumari et al (2022) presented a novel method for the prediction of diabetes mellitus using deep CNN and long shortterm memory. Rajeswari et al (2019) designed a scheme that relies on Machine learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ability of the long short-term memory (LSTM) network to learn order dependencies in sequence prediction problems in data series [31]- [36] makes it widely used for captioning tasks in generating sentence predictions. Research [37]- [40] utilizes a combination of CNN as feature extraction and LSTM to predict the output based on the order dependencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that utilizing sensor data from a CGM device as the only input, machine learning models may be used to estimate future blood glucose levels and enhance the treatment of diabetic condition [22]- [27]. The last 20 minutes' worth of blood glucose values were used as the input by Pérez-Gandia et al [28] to predict the future blood glucose levels of 15 T1D patients.…”
Section: Introductionmentioning
confidence: 99%